163k views
5 votes
2z -5(z +2) = -8 - 2z

Please explain!! Thank you

User Densil
by
6.0k points

1 Answer

4 votes

Follow PEMDAS.

You would first do your distributive property which is, -5(z+2). You would multiply -5 to z and -5 to 2 which will give you -5z + -10.

so now you have 2z-5z+ -10= -8 - 2z. Now you must isolate the variable. So subtract -8 to -10 which will give you -18.

Now you have the equation 2z-5z-18=-2z

Now combine like terms. 2z-5z= -3z

Now you have the equation -3z-18=-2z

Now you must move the -3z to the other side of the equal sign by adding the opposite which is +3z to -2z which will give you +1z

Now you have -18= 1z

Now you divide. -18 divided by 1 is -18.

So your final answer will be -18=z

User Felipe Malara
by
6.3k points